The Functional Role of Lactoferrin in Intestine Mucosal Immune System and Inflammatory Bowel Disease - Liu, Ning; Feng, Gang; Zhang, Xiaoying; Hu, Qingjuan; Sun, Shiqiang; Sun, Jiaqi; Sun, Yanan; Wang, Ran; Zhang, Yan; Wang, Pengjie; Li, Yixuan (Frontiers in Nutrition, 2021)
Inflammatory bowel disease (IBD), encompassing ulcerative colitis (UC) and Crohn’s disease (CD), is one of the main types of intestinal inflammatory diseases with intestine mucosal immune disorder. Intestine mucosal immune system plays a remarkable and important role in the etiology and pathogenesis of IBD. Therefore, understanding the intestine mucosal immune mechanism is a key step to develop therapeutic interventions for IBD. Intestine mucosal immune system and IBD are influenced by various factors, such as inflammation, gut permeability, gut microbiota, nutrients, and so on. Among these factors, emerging evidence show that nutrients play a key role in inflammation activation, integrity of intestinal barrier and immune cell modulation. Lactoferrin (LF), an iron-binding glycoprotein belonging to transferrin family, is a dietary bioactive component abundantly found in mammalian milk. Notably, LF has been reported to perform diverse biological functions including antibacterial activity, anti-inflammatory activity, intestinal barrier protection and immune cell modulation, and is involved in maintaining intestine mucosal immune homeostasis. The improved understanding of the properties of LF in intestine mucosal immune system and IBD will facilitate its application in nutrition, clinical medicine, and health. Herein, this review outlines recent advancements on LF as a potential therapeutic intervention for IBD associated with intestine mucosal immune system dysfunction. We hope this review could provide a reference for future studies and lay a theoretical foundation for LF-based therapeutic interventions for IBD by understanding particular effects of LF on intestine mucosal immune system.